1983
DOI: 10.1002/jctb.280330105
|View full text |Cite
|
Sign up to set email alerts
|

A tubular bioreactor for photosynthetic production of biomass from carbon dioxide: Design and performance

Abstract: A theory of photobioreactor design is developed. A photobioreactor was constructed in the form of a loop made from 52 m of glass tubing of 1 cm bore; the loop covered about 0.5 m2. The culture was illuminated with mercury halide lamps to reproduce sunlight. Computer control was used to maintain constant biomass concentration. The influence of radiation on the reactor temperature is quantitatively predicted. An air lift system was preferred to a liquid pump for culture recycle. The energy required for culture r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(36 citation statements)
references
References 12 publications
(4 reference statements)
0
34
0
2
Order By: Relevance
“…Note, however, that the costs of closed systems are substantially higher than their open pond counterparts [54]. A variety of closed photobioreactors have been tested (or at least proposed) for industrial microalgal biomass production [64,65], but engineering and economic analyses of such reactors still lag behind the open ponds [66][67][68][69][70].…”
Section: Closed Cultivation Systemsmentioning
confidence: 99%
“…Note, however, that the costs of closed systems are substantially higher than their open pond counterparts [54]. A variety of closed photobioreactors have been tested (or at least proposed) for industrial microalgal biomass production [64,65], but engineering and economic analyses of such reactors still lag behind the open ponds [66][67][68][69][70].…”
Section: Closed Cultivation Systemsmentioning
confidence: 99%
“…With respect to this key problem, several steps marked the evolution of the horizontal tubular PBRs since this design appeared in the late 1970s (e.g. Jüttner 1977;Pirt et al 1983). Typically, movement and mass transfers took place in a gas lift in which the culture passed every 10 min in order to limit the dissolved oxygen concentration at peak sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Pirt et al (1983) suggested that ratios around 129 m 2 m −3 are desirable for optimizing the light utilization efficiency in microalgae. Torzillo (1997) reported that suitable photosynthetic rates would be achieved in tubular photobioreactors with a diameter of 2.6 cm operated at a linear velocity of around 30 cm s −1 with air stripping cycle every 6 min.…”
Section: Introductionmentioning
confidence: 99%